ESTIMATION OF GROWTH PATTERN WITH FATTY ACIDS PROFILES IN Labeo rohita (HAMILTON, 1822) USING OF VALUE ADDED FEED - KAR, AVIJIT; CHINI, DEEP SANKAR; BHATTACHARYA, MANOJIT; SAHA, JAYANTA KUMAR; PATRA, SHAMPA; PATRA, BIDHAN CHANDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
An expansion in the escalated culture of numerous freshwater fishes puts a huge interest in production as well as draws special interest on enhancing the eicosapentacenoic acid and docasahexaenoic acid in Labeo rohita due to its numerous benefits for human health. The study has performed to determine the fatty acids profile and composition in L. rohita (insitu trial and experimental) in different experimental time period (initial, 90 days and 180 days) by using of value added feed like flaxseed (α-linolenic acids, 51.26% – 54.94%) and soybean oil (α-linolenic acids, 7.95%-9.01%) as omega-3 supplements. The experimental set-up comprised of control and experimental tanks where 20 number fish are taken for monoculture with same size and age in each tank in which water parameters are regulated in prescribed range. To determine the specific growth pattern LWRs are analyzed where it’s showed positive allometric growth (b=3.22 in 90 days, b=3.11 in 180 days). The GC/MS method also confirmed that the percentages of EPA and DHA increased significantly in experimental (0.87±0.23, initial; 1.95±0.09, 90 days; 5.93±0.10, 180 days) fishes rather than controls (0.87±0.23, initial; 0.99±0.05, 90 days; 4.36±0.10, 180 days). Therefore, it is clearly indicates that, formulated diet performed significantly to maintain the positive allometric growth as well as successive enrichment of PUFAs in experimental specimens which is beneficial for human health as high source of protein and PUFAs as well.